A comparison of early and late treatments on allodynia and its chronification in experimental neuropathic pain. Issue 1 (January 2018) - Salvat, Eric; Yalcin, Ipek; Muller, André; Barrot, Michel
Background: Surgeries causing nerve injury can result in chronic neuropathic pain, which is clinically managed by using antidepressant or anticonvulsant drugs. Currently, there is a growing interest for investigating preemptive treatments that would prevent this long-term development of neuropathic pain. Our aim was to compare analgesic drugs using two distinct treatment modalities: either treatment onset at surgery time or following a couple of weeks of neuropathic pain. Methods: In male C57BL/6J mice, neuropathic pain was induced by cuffing the sciatic nerve, and allodynia was assessed using von Frey filaments. We tested the effect of anticonvulsants (gabapentin 10 mg/kg and carbamazepine 40 mg/kg), antidepressants (desipramine 5 mg/kg, duloxetine 10 mg/kg, and fluoxetine 10 mg/kg), dexamethasone (2 mg/kg), and ketamine (15 mg/kg). Drugs were injected daily or twice a day, starting either at surgery time or on day 25 postsurgery (15 days of treatment for antidepressants and 10 days for other drugs). Results: Ketamine was the only effective treatment during the early postsurgical period. Although early anticonvulsant treatment was not immediately effective, it prevented chronification of allodynia. When treatments started at day 25 postsurgery, desipramine, duloxetine, and anticonvulsants suppressed the mechanical allodynia. Conclusions: Our data show that allodynia measured in experimental neuropathic pain model likely results from a combination of different processes (early vs. late allodynia) that display different sensitivity to treatments. We also propose that early anticonvulsant treatment with gabapentin or carbamazepine may have a prophylactic effect on the chronification of allodynia following nerve injury.